2001
DOI: 10.1081/ceh-100102660
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure Monitoring and Clinical Characteristics of the True and White-Coat Resistant Hypertension

Abstract: The resistant hypertension has been differentiated in true resistant hypertension and white-coat resistant hypertension by using ambulatory blood pressure monitoring. White-coat resistant hypertension was defined as high clinic blood pressure, despite triple treatment for at least 3 months, but day-time blood pressure values < 135/85 mmHg. The aim of this study was to evaluate the presence of different clinical characteristics between two types of resistant hypertension. The study group consisted of 49 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…In 2008, the American Heart Association (AHA) published a scientific statement [16] on a sub-class of hypertensive patients considered to have treatment-resistant hypertension, defined as having uncontrolled blood pressure despite the use of antihypertensive medications from three or more classes, or the use of four or more antihypertensive medication classes to achieve blood pressure control. ABPM is currently recommended for the evaluation of patients with treatment-resistant hypertension [3], as it can determine which patients have white coat resistant hypertension [17, 18]. In adjusted models, having more hypertension diagnoses and filling multiple (particularly 4 or more) classes of antihypertensive medication were associated with a significantly higher likelihood of having an ABPM claim.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, the American Heart Association (AHA) published a scientific statement [16] on a sub-class of hypertensive patients considered to have treatment-resistant hypertension, defined as having uncontrolled blood pressure despite the use of antihypertensive medications from three or more classes, or the use of four or more antihypertensive medication classes to achieve blood pressure control. ABPM is currently recommended for the evaluation of patients with treatment-resistant hypertension [3], as it can determine which patients have white coat resistant hypertension [17, 18]. In adjusted models, having more hypertension diagnoses and filling multiple (particularly 4 or more) classes of antihypertensive medication were associated with a significantly higher likelihood of having an ABPM claim.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this, certain studies demonstrate that patients with true RH have also increased ambulatory pulse pressure in comparison with those with white coat RH [6, 16]. Interestingly ambulatory 24-hour, daytime, and nighttime heart rate is higher in true resistant hypertensives, supporting the notion that increased sympathetic activation may be present in true RH [16]. …”
Section: Abpm Characteristics Of Resistant Hypertensivesmentioning
confidence: 95%
“…In another study, Veglio et al [32] performed ABPM in 49 patients with resistant hypertension (office BP > 140/ 90 mmHg for at least 3 months despite triple drug therapy in near maximal doses, including a diuretic). According to the cutoff values suggested by Pickering (135/85 mmHg for daytime ambulatory BP), the investigators identified 61 % of the study patients with true resistant hypertension (daytime ambulatory BP≥ 135/85 mmHg) and 39 % with white-coatresistant hypertension (daytime ambulatory BP < 135/ 85 mmHg).…”
Section: Prevalence Of Resistant Hypertension Based On Abpm Readingsmentioning
confidence: 98%